2021
DOI: 10.1007/s11033-021-06382-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cell isolation methods on the human transcriptome profiling and microbial transcripts of peripheral blood

Abstract: The expression of human and microbial genes serves as biomarkers for disease and health. Blood RNA is an important biological resource for precision medicine and translational medicine. However, few studies have assessed the human transcriptome profiles and microbial communities composition and diversity of peripheral blood from different cell isolation methods, which could affect the reproducibility of researches. We collected peripheral blood from three healthy donors and processed it immediately. We used RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Given these concerns, our study aimed to assess the viability of employing either PFB or SFB samples as substitute RNA sources in transcriptomic analysis. Previous research have demonstrated the influence of pre-analytical factors on RNA quality and gene expression (Debey-Pascher et al 2011;Mastrokolias et al 2012;Dvinge et al 2014;Shin et al 2014;Zhao et al 2014;Huang et al 2017;Reust et al 2018;Shen et al 2018;Donohue et al 2019;Gautam et al 2019;He et al 2019b;Harrington et al 2020;Xing et al 2021;Chebbo et al 2022;Husseini et al 2022). However, a comprehensive understanding of the similarities and differences among WB, PFB, and SFB samples in transcriptomic research remains elusive, making it crucial to evaluate their suitability for various applications using reliable metrics.…”
Section: Introductionmentioning
confidence: 99%
“…Given these concerns, our study aimed to assess the viability of employing either PFB or SFB samples as substitute RNA sources in transcriptomic analysis. Previous research have demonstrated the influence of pre-analytical factors on RNA quality and gene expression (Debey-Pascher et al 2011;Mastrokolias et al 2012;Dvinge et al 2014;Shin et al 2014;Zhao et al 2014;Huang et al 2017;Reust et al 2018;Shen et al 2018;Donohue et al 2019;Gautam et al 2019;He et al 2019b;Harrington et al 2020;Xing et al 2021;Chebbo et al 2022;Husseini et al 2022). However, a comprehensive understanding of the similarities and differences among WB, PFB, and SFB samples in transcriptomic research remains elusive, making it crucial to evaluate their suitability for various applications using reliable metrics.…”
Section: Introductionmentioning
confidence: 99%
“…Given these concerns, our study aimed to assess the suitability of employing either PFB or SFB samples as alternative RNA sources in transcriptomic analysis. Previous researches have demonstrated the influence of pre-analytical factors on RNA quality and gene expression (Debey-Pascher et al 2011 ; Mastrokolias et al 2012 ; Dvinge et al 2014 ; Shin et al 2014 ; Zhao et al 2014 ; Huang et al 2017 ; Reust et al 2018 ; Shen et al 2018 ; Donohue et al 2019 ; Gautam et al 2019 ; He et al 2019a ; Harrington et al 2020 ; Xing et al 2021 ; Chebbo et al 2022 ; Husseini et al 2022 ). However, a comprehensive understanding of the similarities and differences among WB, PFB, and SFB samples in transcriptomic profiles remains elusive, making it crucial to evaluate their suitability for various applications using reliable performance metrics.…”
Section: Introductionmentioning
confidence: 99%